Development of Integrated Service Innovation (myITS Services) at the Integrated Service Center of Institut Teknologi Sepuluh Nopember - Nurfiana, Ellif; Umiyati, Sri; Wahyuni, Sri (Journal Public Policy, 2025)
This study aims to analyze the development of integrated service innovation through the myITS Services platform at the Integrated Service Center (ISC) of Institut Teknologi Sepuluh Nopember (ITS) in an effort to enhance the effectiveness and efficiency of public services in the academic environment. Using a qualitative descriptive approach, data were collected through document analysis, interviews, and observations. The findings were systematically analyzed using SWOT, IFAS, and EFAS matrices to map strategic positions and improvement priorities. The results show that the integration of myITS Services, supported by leadership commitment and an innovation-driven organizational culture, has significantly improved service quality and customer satisfaction at ITS. Internal strengths include advanced information technology utilization and strong cross-unit collaboration, while structural weaknesses persist, such as limited human resource capacity and data ownership egocentrism among units. External challenges involve regulatory changes and the need for robust data security management. This study concludes that digital service innovation, when supported by integrated governance and collaborative participation, is both feasible and impactful in the higher education sector. However, the research is limited to a single institution and qualitative scope, suggesting future studies adopt a comparative and quantitative approach to measure efficiency, cost savings, and user satisfaction, as well as explore opportunities for artificial intelligence-based service automation.